Quantifying the Socio-Psychological Impacts of Suicide Bombing on the Victims: A Case Study of Balochistan - Gulshan Munir; Mumtaz Ali; Saima Sheikh (Journal of Management Practices, Humanities and Social Sciences, 2023)
Suicide bombing, a comparatively modern and highly devastating form of terrorism, severely impacts the victims. However, the long-term impacts of such incidents are not comprehensively explored in the context of educational institutes in Balochistan, the largest province of Pakistan. This study empirically quantifies the long-term socio-psychological consequences of suicide bombings on victims in educational institutions, specifically women's universities in Balochistan, by analyzing the 2013 suicide bombing attack on the Sardar Bahadur Khan Women's (SBKW) University in Quetta, Pakistan. The study was conducted using a quantitative research design approach where the primary data was collected from a random representative sample of 357 direct victims using a cross-sectional survey approach. The questionnaire captured various socio-psychological variables such as trauma, doubtfulness, social support and isolation, and coping mechanisms, while different inferential statistical analyses, such as regression, correlation, and ANOVA tests, were employed to evaluate the relationships between variables. Our analysis revealed that victims of the SBKW University suicide bombing experienced significant psychological distress and social dissatisfaction with a strong correlation of r = 0.16, p < 0.001, and r = 0.19, p < 0.001, respectively. This study provides a quantitative understanding of the long-term impacts of suicide bombings on victims to inform policy development and intervention strategies. Overall, this research provides nuanced insights into the complex effects of suicide bombings on victims by highlighting the need for improved security measures and resilience-building initiatives and underscoring the need to address their socio-psychological well-being in post-conflict an post-disaster contexts